2014
DOI: 10.2147/ppa.s69680
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study on hypertensive care behavior in primary health care settings in Malaysia

Abstract: PurposeThe aim of this study was to explore patients’ experiences with their illnesses and the reasons which influenced them in not following hypertensive care recommendations (antihypertensive medication intake, physical activity, and diet changes) in primary health clinic settings.Patients and methodsA qualitative methodology was applied. The data were gathered from in-depth interviews with 25 hypertensive patients attending follow-up in nine government primary health clinics in two districts (Hulu Langat an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(65 citation statements)
references
References 27 publications
4
60
0
1
Order By: Relevance
“…The present study showed that physicians and medical team's commitments, skills, and behaviors had special motivational effect on patients’ adherence behaviors. Similarly, earlier researches ( 9 , 10 , 12 , 15 , 17 , 38 , 40 , 44 46 ) reported that trust in a doctor and a mutual patient–provider relationship facilitated adherence to the treatment. Based on the findings, other Iranian healthcare organizational factors that affect treatment adherence included lack of accessible care, suitable medicines, and follow-up systems.…”
Section: Discussionmentioning
confidence: 51%
“…The present study showed that physicians and medical team's commitments, skills, and behaviors had special motivational effect on patients’ adherence behaviors. Similarly, earlier researches ( 9 , 10 , 12 , 15 , 17 , 38 , 40 , 44 46 ) reported that trust in a doctor and a mutual patient–provider relationship facilitated adherence to the treatment. Based on the findings, other Iranian healthcare organizational factors that affect treatment adherence included lack of accessible care, suitable medicines, and follow-up systems.…”
Section: Discussionmentioning
confidence: 51%
“…A significant correlation between beliefs about medication and MNA was found among hypertensive patients in Ghana and Nigeria [26] with patients who were worried about the adverse effects of antihypertensive drugs less likely to be adherent to their medications (r = −0.0347, P = 0.002). Qualitative studies in Pakistan [39] and Malaysia [51] also found patients hesitated to take medications continuously due to their lack of belief in medications. As one hypertensive patient in Pakistan commented: "Medications are hot (warm) in nature.…”
Section: Perceptions Regarding Hypertension and Its Severitymentioning
confidence: 99%
“…Qualitative studies in Malaysia [51] and Nigeria [40] also found perceived side effects were inhibitors of antihypertensive medication adherence. However, Praveen et al [30] in India did not find a correlation between adverse drug events and non-adherence.…”
Section: Mmas 4 Ethiopia; N = 384 Open Journal Of Epidemiologymentioning
confidence: 99%
“…A qualitative study on patient perspective of hypertension done in Canada found that patients struggled to define hypertension; only half of them (54%) could recall their targeted blood pressure threshold 12. Other qualitative studies conducted in Malaysia13 and the USA14 reported that their patients were not aware that hypertension could be asymptomatic, and the asymptomatic patients considered themselves healthy. Furthermore, patients believed that hypertension can be cured and that they can discontinue medicine when their blood pressure is normal 6 15–17.…”
Section: Introductionmentioning
confidence: 99%